(untitled) (African Journal of Biomedical Research, 2024)
The presence of pathogenic microorganisms in hospital environment possesses obvious clinical risk to patients with some obvious consequences. The current study was conducted to ascertain the prevalence of Pseudomonas aeruginosa in nonclinical samples in central Hospital, Agbor. A total of 25 Pseudomonas aeruginosa were isolated from a total of 110 nonclinical samples collected intermittently from Sinks traps, Mop heads, bed pans from four (4). The samples were inoculated on MacConkey and blood agar plates and incubated at 37 °C for 24 h. The isolates were identified by conventional microbiological tests. Antimicrobial susceptibility pattern was determined by modified Kirby-Bauer disk diffusion method. The overall prevalence of Pseudomonas aeruginosa was 23.8% with a range of 16.2% to 33.2% in the wards examined. The most contaminated area with Pseudomonas aeruginosa was sink traps (36.)%), floors (24.0%), mopheads (20.0%) while bedpans accounted for 20.0% of the isolate sources. the antibacterial susceptibility patterns of the Pseudomonas aeruginosa to ten (10) antibacterial agents used showed 84% susceptibility to pefloxacin, 76% to ofloxacin, while ceftriaxone and ciprofloxacin recorded 72% susceptibility respectively. 64% of the isolates were susceptible to gentamicin. The continued contamination of hospital wards with Pseudomonas aeruginosa highlights the necessity for robust infection control measures, ongoing monitoring and management of the hospital environment to minimize the risk of healthcare-associated infections